Igneous Rock Associations 15. The Columbia River Basalt Group: A Flood Basalt Province in the Pacific Northwest, USA - Reidel, Stephen (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2015)
The middle Miocene Columbia River Basalt Group (CRBG) is the youngest, smallest, and best-preserved continental flood-basalt province on Earth. The CRBG covers ~ 210,000 km2 of the Pacific Northwest, USA near the British Columbia border. CRBG consists of ~ 210,000 km3 of basalt that began erupting ~ 16.7 Ma in the southern part of the province with younger eruptions progressively migrating northward; the last eruption occurred at ~ 5 Ma. The CRBG consists of seven formations. The Steens Basalt is the oldest but the next oldest, the Imnaha Basalt, began erupting near the end of the Steens volcanic episode. After a short hiatus at the end of the Imnaha Basalt, the Grande Ronde Basalt began to erupt. Both the Picture Gorge Basalt and Prineville Basalt erupted simultaneously with the Grande Ronde Basalt. The Steens, Imnaha, and Grande Ronde Basalts are the main phase of the eruptions representing ~ 94% of the CRBG volume. The Wanapum Basalt followed the Grande Ronde Basalt, which in turn was followed by the Saddle Mountains Basalt, the final phase of the eruptions. The formations, members and many flows of the CRBG can be identified by using a combination of major, minor and trace element compositions, lithology, magnetic polarity, and stratigraphic position. This allows the aerial extent and volume of the individual flows and groups of flows to be calculated and correlated with their respective dykes and vents. The eruption and emplacement rate of the flows has been controversial, with various lines of evidence suggesting that some flows erupted very rapidly and others probably erupted over much longer periods of time. The CRBG was probably derived from a mantle plume, although this conclusion is controversial. Compositions indicate the CRBG magmas underwent varying degrees of recharge, contamination, and fractionation prior to each eruption. Although the peak eruptions occurred during the middle Miocene Climatic Optimum, at present no significant extinction or environmental consequence has been correlated with the CRBG.